Gaya Mengajar Dosen Terhadap Motivasi Belajar Mahasiswa Di Era New Normal Covid-19 - Destia Mustikasari; Mochamad Rizki Subagja; Ramdan Inda Majid (IHSA Institute, 2022)
This study aims to determine the teaching style of lecturers on student learning motivation at the Islamic University of Nusantara Bandung, the study program of communication science. The type of research used in this research is descriptive with a qualitative approach. The data collection method in this study was carried out by distributing questionnaires to 15 Uninus students of the communication science study program at random, and conducting a survey on the answers from the 15 resource persons. From the results of this study, almost 100% of the informants agreed that the teaching style of lecturers in the new normal era was very influential on understanding a material and their learning motivation. The more attractive the lecturer's teaching style, the easier it is to understand the material.